Ecological patterns of blood-feeding by kissing-bugs (Hemiptera: Reduviidae: Triatominae) - Rabinovich, Jorge (2011)
Host use by vectors is important in understanding the transmission of zoonotic diseases, which can affect hu mans, wildlife and domestic animals. Here, a synthesis of host exploitation patterns by kissing-bugs, vectors of Cha gas disease, is presented. For this synthesis, an extensive literature review restricted to feeding sources analysed by precipitin tests was conducted. Modern tools from community ecology and multivariate statistics were used to de termine patterns of segregation in host use. Rather than innate preferences for host species, host use by kissing-bugs is influenced by the habitats they colonise. One of the major limitations of studies on kissing-bug foraging has been the exclusive focus on the dominant vector species. We propose that expanding foraging studies to consider the com munity of vectors will substantially increase the understanding of Chagas disease transmission ecology. Our results indicate that host accessibility is a major factor that shapes the blood-foraging patterns of kissing-bugs. Therefore, from an applied perspective, measures that are directed at disrupting the contact between humans and kissing-bugs, such as housing improvement, are among the most desirable strategies for Chagas disease control.